Production of titanium and titanium dioxide from ilmenite and related applications. (Patent landscape report, 2023)
This report provides a landscape of the patent activity on the process of extracting titanium dioxide or titanium metal from ilmenite ore. In addition, a section on the industrial applications of titanium dioxide and titanium metal focuses on selected applications, such as ceramics, medical technology, electrodes for batteries, cosmetics, coatings and water treatment. This WIPO Patent Landscape Report aims to help policy and decision makers identify opportunities for ilmenite processing technologies and applications.